Variable embodiment of stance-taking and footing in simultaneous interpreting - Cienki, Alan (Frontiers in Psychology, 2024)
Previous research has argued that consecutive interpreters constitute laminated speakers in the sense that they engage with different kinds of footing at once, representing another's point of view through their words in another language. These multiple roles also play out in their gesturing, as they sometimes indicate deictically who is the source of the ideas and stances they are expressing (the principal). Simultaneous interpreters, though, often work in an interpreting booth; they are often not seen by the audience, yet many of them gesture, sometimes frequently. How are simultaneous interpreters using gesture in relation to stance-taking and footing? We consider the case of simultaneous interpreters rendering popular science lectures between (both to and from) Russian (their L1) and either English or German (their L2). Though only hearing the audio of the lectures, the interpreters produced many gestures, which were analyzed for their function. Some representational and deictic gestures appeared to clearly involve the interpreter as the principal (writing numbers with one's finger to help remember them or pointing to two places on the desk to keep track of two different quantities mentioned). Other representational and deictic gestures are ambiguous as to whether they are enacting what the interpreter may have imagined what the lecturer did or whether they arose out of the interpreter's own thinking for speaking (e.g. tracing the form of a bird being mentioned or pointing to an empty space when the lecturer was referring to a graph). Pragmatic gestures, showing one's stance towards the topic of the talk, were the most ambiguous as to the footing, reflecting how the interpreter may be engaged in fictive interaction with their imagined audience. Self-adapters, however, more clearly involve the interpreter as the principal, as such actions are known to support cognitive focussing and self-soothing. In sum, we see varying degrees of clarity as to whose stance and principal footing simultaneous interpreters are expressing bodily as laminated speakers. The variable ambiguity can be attributed to the nature of gesture as a semiotic system, the functions of which are more often dependent on co-occurring speech than vice versa.